The impact of increased international migration on French immigration policy - Snisarenko, Konstantin (Journal of the Belarusian State University. International Relations, 2024)
In this article the author looks into the transformation of French immigration policy under the influence of burgeoning international migration. Initially focused on controlling of labour market access, the policy has evolved to encompass immigrant integration and citizenship criteria. This shift marks a transition from restrictive to selective immigration regulation, with the French establishment viewing it as a means to depoliticise the immigration issue. However, the challenge of successfully integrating of non-European immigrants into French society remains unresolved, largely due to the perceived supremacy of French culture over those of African and Asian origins.
Keywords: international migration; immigration policy; migration networks; imagined community; France